2014
DOI: 10.1186/1471-2350-15-81
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogen related receptor beta (ESRRB) in DFN35B hearing impairment and dental decay

Abstract: BackgroundCongenital forms of hearing impairment can be caused by mutations in the estrogen related receptor beta (ESRRB) gene. Our initial linkage studies suggested the ESRRB locus is linked to high caries experience in humans.MethodsWe tested for association between the ESRRB locus and dental caries in 1,731 subjects, if ESRRB was expressed in whole saliva, if ESRRB was associated with the microhardness of the dental enamel, and if ESRRB was expressed during enamel development of mice.ResultsTwo families wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 44 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…Therefore, they often intentionally avoid sweet food and, subsequently, have low caries intensity [Shuler, 2001]. Interesting research was presented by Weber et al [2014]; however, it was not included in the review because of a different type of gene analysed. They examined the ESRRB gene for the oestrogen-related receptor-β, the mutation of which can lead to hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they often intentionally avoid sweet food and, subsequently, have low caries intensity [Shuler, 2001]. Interesting research was presented by Weber et al [2014]; however, it was not included in the review because of a different type of gene analysed. They examined the ESRRB gene for the oestrogen-related receptor-β, the mutation of which can lead to hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene have also been associated with hearing impairment and dental decay 35 . In addition, upregulation of ESRRB has been linked with the progression of endometriosis 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work aimed to explore the role of ESRRB in the oral tissues and found the association of this gene with caries susceptibility as well as its expression in the salivary gland and in the enamel development [Weber et al, 2014]. ESRRB is expressed in enamel development and could have a role in the calcium composition in the enamel.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the association between ESRRB and calcium level in saliva is through the salivary gland function. Although we demonstrated that this gene is expressed in salivary gland [Weber et al, 2014], its role in salivary function is still unknown.…”
Section: Discussionmentioning
confidence: 99%